Screening for Active Compounds Targeting Human Natural Killer Cell Activation Identifying Daphnetin as an Enhancer for IFN-γ Production and Direct Cytotoxicity - Yao, Baige; Yang, Qinglan; Yang, Yao; Li, Yana; Peng, Hongyan; Wu, Shuting; Wang, Lili; Zhang, Shuju; Huang, Minghui; Wang, Erqiang; Xiong, Peiwen; Luo, Ting; et al. (Frontiers in Immunology, 2021)
Natural killer (NK) cells are a potent weapon against tumor and viral infection. Finding active compounds with the capacity of enhancing NK cell effector functions will be effective to develop new anti-cancer drugs. In this study, we initially screened 287 commercially available active compounds by co-culturing with peripheral blood mononuclear cells (PBMCs). We found that five compounds, including Daphnetin, MK-8617, LW6, JIB-04 and IOX1, increased the IFN-γ+ NK cell ratio in the presence of IL-12. Further studies using purified human primary NK cells revealed that Daphnetin directly promoted NK cell IFN-γ production in the presence of IL-12 but not IL-15, while the other four compounds acted on NK cells indirectly. Daphnetin also improved the direct cytotoxicity of NK cells against tumor cells in the presence of IL-12. Through RNA-sequencing, we found that PI3K-Akt-mTOR signaling acted as a central pathway in Daphnetin-mediated NK cell activation in the presence of IL-12. This was further confirmed by the finding that both inhibitors of PI3K-Akt and its main downstream signaling-mTOR, LY294002 and rapamycin, respectively, can reverse the increase of IFN-γ production and cytotoxicity in NK cells promoted by Daphnetin. Collectively, we identify a natural product, Daphnetin, with the capacity of promoting human NK cell activation via PI3K-Akt-mTOR signaling in the presence of IL-12. Our current study opens up a new potential application for Daphnetin as a complementary immunomodulator for cancer treatments.